EPR linewidth of local magnetic moments diluted in Ce intermediate-valence compounds - Venegas, Pablo Antonio [UNESP]; Barberis, Gaston E. (American Physical Society (APS), 1992)
Anomalous thermal behavior on the EPR linewidths has been observed for Gd impurities diluted in CexA1-xBn (A=La,Y, B=Ir,Os,Rh,Pd) intermediate-valence compounds. In this work we show that the exchange interaction between the local magnetic moments and the intermediate-valence host ions has an important contribution to the relaxation rates of the local moments. We calculated the relaxation, using the Redfield formalism and the ideas contained in the interconfigurational fluctuation model of Hirst. We show that the exchange interaction contribution has an exponential dependence on the excitation energy of the intermediate-valence ions. © 1992 The American Physical Society.